Chapter Continuous Anything for Distributed Research Projects - Griesinger, Frank (InTechOpen, 2018)
International research projects involve large, distributed teams made up from multiple institutions. These teams create research artefacts that need to work together in order to demonstrate and ship the project results. Yet, in these settings the project itself is almost never in the core interest of the partners in the consortium. This leads to a weak integration incentive and consequently to last minute efforts. This in turn results in Big Bang integration that imposes huge stress on the consortium and produces only non-sustainable results. In contrast, industry has been profiting from the introduction of agile development methods backed by Continuous Delivery, Continuous Integration, and Continuous Deployment. In this chapter, we identify shortcomings of this approach for research projects. We show how to overcome those in order to adopt all three methodologies regarding that scope. We also present a conceptual, as well as a tooling framework to realise the approach as Continuous Anything. As a result, integration becomes a core element of the project plan. It distributes and shares responsibility of integration work among all partners, while at the same time clearly holding individuals responsible for dedicated software components. Through a high degree of automation, it keeps the overall integration work low, but still provides immediate feedback on the quality of the software. Overall, we found this concept useful and beneficial in several EU-funded research projects, where it significantly lowered integration effort and improved quality of the software components while also enhancing collaboration as a whole.